DIRECTIONS AND CONDITIONS FOR SOLVING TOPICAL ISSUES OF LINGUISTIC SUPPORT FOR FORCES UNDER THE CONDITIONS OF MARTIAL LAW IN UKRAINE - Sameliuk, A.; Tychyna, I.; Mitkina, Y. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
LSF is interpreted quite ambiguously within Ukrainian scientific discourse. The term lacks clarity in delineating a single meaning, systematic use and pronounced tendency towards ambiguity within the sectoral (philological-pedagogical and military-pedagogical) conceptual field. Currently, LSF covers completely communicative and functional spectrum related to the military area. However, they primarily mean studies of military translation and Ukrainian military’s foreign language training (especially in English). The aim of the present research is to outline the actual concerns and concepts of the linguistic support for forces (LSF) throughout the wartime, to outline the tasks of the LSF in the focus of present events in Ukraine and, in particular, in the educational process of the military in the state of full-scale war. In addition, there is a purpose to focus on those topical questions of the LSF, which have arisen or acquired aggravation with the beginning of the Russian-Ukrainian war confrontation. It was found that war always has a worldwide global essence. Even though it is concentrated locally in geographical dimension (like in Ukraine). Therefore, in the paradigm of up-to-date war events and their effects, language as an instrument of understanding and cooperating between various participants of war has a wide range of extremely important functions. Especially while speaking about foreign languages, which play an indispensable operating and strategic, additionally also ideological role in war narratives. The works of prominent scientists on the subject of LSF identifies promising directions for the improvement of LSF in Ukraine. They were analyzed in the article. The significance of implementing special computer technics and software into the LSF field was highlighted. This would fasten the process of working out the large layers of information and allows having quick essential communication in a timely manner. Under the conditions of martial law adequate messaging is necessary. Whether in real time or under situations of remote (asynchronous) communicative interaction. In the field of foreign language training of the military as one of the fundamental problem of LSF as a discipline and field of knowledge, it has been observed that the tendencies to train the military in an authentic foreign language environment are maintained. The very format of such acquisition of foreign language competences appears in current literature (scientific, special, in the documentation of the Armed Forces of Ukraine, etc.) as the most advantageous for successful language training of military personnel. In addition, learning in reliable foreign language surroundings contributes to compliance with NATO canons.